Unclear effect of Omega-3 polyunsaturated fatty acid supplementation on speed-skating performance - Noordhof, D. A.; van Ginkel, S. L.; Levels, K.; van der Zwaard, S.; Hofmijster, M. J.; van der Laarse, W. J.; de Ruiter, C. J.; Jaspers, R. T.; de Koning, J. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Elite speed skaters need to be able to generate a high peak power output and to sustain a high power output for the duration of the race; they therefore combine resistance-type training with endurance training. Combining these training modalities results in a smaller increment in muscle strength than when only resistance-type training is performed.